Analytical and numerical modelling of biomass gasification in downdraft gasifiers. Issue 1 (1st April 2022) - Moretti, L; Arpino, F.; Cortellessa, G.; Dell'Isola, M.; Ficco, G; Grossi, G.; Zuena, F.; Di Palma, M.; Vanoli, L.
Abstract: The ever-growing energy demand and environmental pollution level have pushed research interest toward the development of new promising technologies to utilize bioenergy sustainably. In this scenario, biomass gasification has been regarded as a promising renewable energy resource that, if efficiently exploited, can contribute to the reduction of dependency on fossil fuel and CO2 emissions from the power sector. Nevertheless, exploitation of biomass gasification still requires to overcome technological and logistical issues. In this work, the authors propose a general thermodynamic model able to predict the steady operating conditions of biomass gasification. Assuming thermodynamic equilibrium, the model is able to predict temperature, mass flow rate and composition of produced syngas. Moreover, a numerical model of the biomass gasification system has been developed by using the commercial software Aspen Plus. It is a steady-state zero-dimensional equilibrium model, based on the mass and energy balances, assuming the Gibbs free energy minimization. Aspen Plus allows building models of customized operative units using the Fortran code. In order to assure the performance of both analytical and Aspen Plus models, numerical results are compared with experimental data available in the scientific literature for downdraft gasifiers.